Applying norms and preferences for designing flexible game rules. (2015) - Booth, Edward; Thangarajah, John; Zambetta, Fabio
Interactive storytelling is a strength of table-top role playing games as they are facilitated by a game master (GM) who directs the narrative and devises game scenarios. One difficulty with the implementation of a GM in computer games is the large amount of time, effort and specialist skills that can be required for the creation of such an agent. Another issue is that game rules become embedded in the agent implementation and thus may become difficult and time consuming to change. This article aims to address these issues by presenting a method for developers to shape the narrative by defining game behaviour in terms of norms and preferences. The system was evaluated with both a case study and a user experiment. The results showed that the users found out the system to be both user friendly and suitable for development of games with flexible narrative.